The Impact of a Horizontal Versus Vertical Product Display on the Attraction Effect - Kim, Jungkeun; Park, Jongwon; Oppewal, Harmen (Journal of Marketing Research, 2026)
Marketers can display their products horizontally or vertically in both online and offline settings. This display orientation has been shown to influence consumers’ judgments about individual products. The present research extends the literature by investigating the moderating impact of display orientation on the attraction effect, one of the most well-established context effects in choice. A total of 11 studies, including 7 preregistered experiments, document a novel finding that the attraction effect is stronger when choice alternatives are displayed horizontally rather than vertically. This moderating influence is replicated in both consequential choices and hypothetical scenarios and shown to generalize over diverse product categories. The authors explain this influence by proposing that a horizontal (vs. vertical) display increases the ease of comparing choice alternatives, leading consumers to notice the asymmetric dominance relationship among them more easily. Consistent with this mechanism, the authors find that the moderating influence of display orientation attenuates when individuals are guided to recognize the asymmetric dominance relationship or when their ability to compare vertically displayed products is momentarily enhanced. The present research thus demonstrates a significant effect of spatial orientation on the comparison and evaluation of alternatives. Theoretical and managerial implications of findings are discussed.